Hybrid Warfare in Democratic Instability: Technology, Information Operations, and International Security - Marsili, M. (XIII Portuguese Congress of Sociology (XIII APS), 2025)
The growing instability of democratic systems, combined with evolving forms of warfare, has created an urgent need to reexamine the intersection of security, technology, and information operations. Hybrid warfare, which operates both above and below the threshold of conventional conflict, takes advantage of technological advances in cybersecurity, cognitive warfare, and disinformation, further destabilizing already fragile democracies. Drawing on recent case studies, this paper explores how hybrid threats, such as cyber-attacks and cognitive operations, exploit democratic weaknesses, creating new forms of insecurity that transcend national borders. By analyzing current conflicts, such as in Ukraine, this study argues that hybrid warfare not only impacts military strategy but also reshapes international security policies and civilian perceptions of trust in democratic institutions. The paper further investigates how technological advancements can either exacerbate or mitigate the threats posed by hybrid warfare. The research aims to offer a conceptual framework for understanding these dynamics, emphasizing the need for robust security strategies that address both technological and socio-political vulnerabilities.